India's Islamic traditions, 711-1750 - Eaton, Richard Maxwell (New Delhi : Oxford University Press, 2003)
Contributed articles.
Includes bibliographical references (p. [411]-417) and index.
Keywords: Muslims -- India -- History; Islam -- India -- History; India -- Civilization -- To 1200.; India -- Civilization -- 1200-1765.